Clima organizacional y Desarrollo productivo del Gobierno Autónomo Descentralizado Intercultural del cantón Cañar - Achic Pacari, Cungachi Guamán (2024)
ABSTRACT: The organizational climate and productive development in the intercultural decentralized autonomous government of the Cañar canton is a significant factor within government institutions since it serves society. Therefore, it must be within a satisfied work environment. Productive development is on the rise. In this work, both general and specific objectives and hypotheses were proposed to help resolve the study. The theoretical framework describes each variable, allowing us to provide sufficient and necessary knowledge to propose specific strategies for the organizational climate to promote development. Productive in the GADICC of the Cañar canton. Our research methodology was grounded in the hypothetical-deductive method. This approach allowed us to propose and verify our hypotheses through the collection and analysis of data. By doing so, we were able to thoroughly study the research phenomenon and provide a robust solution to the problem at hand in our research work. According to the survey, the organizational climate and productive development variables were analyzed with their respective indicators. They were applied directly to the administrative staff of the GADICC of the Cañar canton, specifically to a sample of 185. The strategy proposed in Chapter VI is based on the need for the institution to function.